Improving Mathematical Meaningful Abilities of Native Students in The Pelabuhanratu Region Using an Ethnomathematics Approach - Rineka Rosinansis; Tatang Herman; Aan Hasanah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Understanding that mathematics is a subject that is difficult to believe because mathematical concepts are abstract and, therefore, difficult to comprehend and understand. Students' abilities and skills in mathematics subjects in Indonesia are relatively low. However, this can only be generalized to some Indonesian students, considering that Indonesia is a large country with many students. This research aims to describe customs, traditions, and culture holistically, then apply them to mathematics learning activities through ethnomathematics studies for indigenous students with the hope that mathematics learning will become more meaningful when studying mathematics. According to Spradley, this research method is descriptive qualitative with an ethnographic approach and a gradual progressive research flow. The result of this research is that the ethnomathematics approach has succeeded in making mathematics, which was often abstract, become real. Indigenous students who study ethnomathematics-based mathematics feel that the mathematics lesson material becomes logically meaningful; students can also absorb the material into their cognitive structure. Indigenous students who learn ethnomathematics-based mathematics can learn mathematical material by interpreting each element of mathematics culture or combining the two into ethnomathematics.